2008
DOI: 10.1103/physreva.77.032713
|View full text |Cite
|
Sign up to set email alerts
|

Orbital sensitivity inMg2+dielectronic recombination calculations

Abstract: We have investigated the reason for significant discrepancies between the results of two recent, similar computational methods ͓Zatsarinny et al., Astron. Astrophys. 426, 699 ͑2004͒; Gu, Astrophys. J. 590, 1131 ͑2003͔͒ for dielectronic recombination ͑DR͒ of Mg 2+. It is found that the choice of orbital description can lead to discrepancies by as much as a factor of 2 between total peak DR rate coefficients resulting from otherwiseidentical computations. These unexpected differences are attributed to the large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A large orbital sensitivity of DR to the choice of the initial radial wave function has been reported in Mg 2+ [13]. For Fe 15+ , this sensitivity is expected to be insignificant as a result of the high q of the ion.…”
Section: Configuration Interaction Between Different N Resonance Cmentioning
confidence: 97%
“…A large orbital sensitivity of DR to the choice of the initial radial wave function has been reported in Mg 2+ [13]. For Fe 15+ , this sensitivity is expected to be insignificant as a result of the high q of the ion.…”
Section: Configuration Interaction Between Different N Resonance Cmentioning
confidence: 97%
“…Another important process is recombination for which a number of new works including radiative and dielectronic recombination have appeared: C 2+ , N 3+ , and O 4+ (Fogle et al 2005); Si 3+ (Schmidt et al 2007); Mg 2+ (Fu et al 2008); and Fe 16+ (Chen 2008). …”
Section: Electron-ion Scatteringmentioning
confidence: 98%
“…Of particular utility, a basis of nonorthogonal orbitals is used where a unique set is optimized for each target, resonance, and bound state, thereby incorporating important term-dependent and relaxation effects. Our earlier work on PR of Mg 2+ [16] and Ti 4+ [13] demonstrated that such a nonorthogonal basis yields accurate energies and transition rates for highly sensitive cases.…”
Section: Autoionizing Transition or Labelmentioning
confidence: 99%